What Does Supervision Help With? A Survey of 315 Social Workers in the UK. Issue 1 (1st January 2019) - Wilkins, David; Antonopoulou, Vivi
Abstract : What does social work supervision help with? There are many different models of supervision and an increasing amount of research. Much of this is concerned with the content of supervision and how supervisors (and supervisees) should behave — and these are important concerns. But even more important is the question of who or what supervision helps with. Supervision is widely considered to have many different functions but in the context of UK local authority social work, must ultimately prove itself as a method for helping people who use services. This article reports on a survey of 315 social workers from UK local authorities. Most reported that supervision helps primarily with management oversight and accountability. However, the small number of practitioners who received regular group supervision and those who received supervision more frequently said it helped with a much broader range of things.